Integrated Management of Kovvada Kalva Watershed, West Godavari District, A.P., India using Remote Sensing & GIS - Rambabu, T; Raghuram, P; Sankara Pitchaiah, P; A.R.K Raju, P (International Journal of Engineering and Technology, 2018)
Watershed management is an integrated approach where a balanced utilization of land and water resources for optimal production with least menace to natural resources. Geospatial Technologies can be played an important role for the organization of various natural resources in a watershed. For sustainable development of land and water resources, the Andhra Pradesh State Government is implementing development of watershed programmes on priority basis. The watershed management activities include construction of rainwater harvesting structures, soil conservation measures and environmental protection measures (TAWDEVA). The selected watershed area was Kovvada Kalava Watershed which is a part of West Godavari District of Andhra Pradesh and was identified as drought and flood effected area because of sparse and variable rainfall. Collection of resource data includes digital imageries of study area for two seasons, Survey of India toposheets on 1:50000 scale, and other ancillary data / maps were conceded along with socio-economic data. The other datasets include levels of groundwater from concerned departments etc was collected. Various thematic maps on Settlements and Transport Network, Contours, Drainage Network, Slope, Geomorphology, Lithology, Structure and Land Use / Land Cover were generated by employing Arc GIS platform. After analyzing all maps integrated watershed analysis has been made aiming at generating sustainable developmental measures of land and water resources in the area.